2017
DOI: 10.3892/ijmm.2017.2939
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of UV-B exposure-induced inflammation by abalone hypobranchial gland and gill extracts

Abstract: Exposure to solar ultraviolet B (UV-B) is a known causative factor for many skin complications such as wrinkles, black spots, shedding and inflammation. Within the wavelengths 280–320 nm, UV-B can penetrate to the epidermal level. This investigation aimed to test whether extracts from the tropical abalone [Haliotis asinina (H. asinina)] mucus-secreting tissues, the hypobranchial gland (HBG) and gills, were able to attenuate the inflammatory process, using the human keratinocyte HaCaT cell line. Cytotoxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This might have been due to the ability of the slime extract to decrease the inflammatory signals that enhance the granuloma formation. It was reported that extracts from snails could decrease plasma IL-6, an inflammatory cytokine in osteoarthritis-induced dog [27] and decrease COX level induced in inflammatory keratinocytes [28] . In the study, the slime extracts also improved the oxidative status of cotton-pellet induced granuloma in rats.…”
Section: Resultsmentioning
confidence: 99%
“…This might have been due to the ability of the slime extract to decrease the inflammatory signals that enhance the granuloma formation. It was reported that extracts from snails could decrease plasma IL-6, an inflammatory cytokine in osteoarthritis-induced dog [27] and decrease COX level induced in inflammatory keratinocytes [28] . In the study, the slime extracts also improved the oxidative status of cotton-pellet induced granuloma in rats.…”
Section: Resultsmentioning
confidence: 99%
“…UV irradiation upregulates various cytokines, such as interleukins (ILs), inducible nitric oxide synthase (i-NOS), and cyclooxygenase (COX)-2, and this consequently stimulates inflammation and results in skin sunburn and erythema. IL and NF-κB upregulate COX-2 expression, causing photodamage of the skin [7].…”
Section: Introductionmentioning
confidence: 99%
“…These particular states are characterized by an upregulated production of inflammatory mediators, alteration of vascular responses, and inflammatory cell infiltration. 74,75 Therefore, the use of natural products with anti-inflammatory activity, such as cinnamon essential oil, 76,77 to alleviate the negative effects of UVB radiation could be of high interest.…”
Section: In Vivo Efficacy Of the Fibrous Dressingsmentioning
confidence: 99%